Peluang dan Tantangan di Era Digital terhadap Praktik Manajemen Keberlanjutan di Sektor Nirlaba - Peniel S. Siregar (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The digital era has transformed many aspects of life, including the way nonprofit organizations operate within the context of sustainability management. Digital technologies, such as blockchain, artificial intelligence (AI), and social media platforms, have opened up new opportunities for the nonprofit sector to improve operational efficiency, expand reach, and optimize resource use. However, behind these opportunities, significant challenges must be addressed. This paper aims to explore the opportunities and challenges facing nonprofit organizations in practicing sustainability management in the digital era. Using a qualitative analysis approach and case studies, we will discuss how digital technology can be used to support sustainability goals, as well as the ethical and practical challenges that arise from its use. Relevant data and statistics will be presented to provide a clearer picture of the impact of digital technology on the nonprofit sector. This research is expected to provide valuable insights for stakeholders in the nonprofit sector in formulating effective strategies to leverage digital technology to achieve their sustainability goals.